Effectiveness of Village Fund Allocation Management in Salo Dua Village, Maiwa District, Enrekang Regency - Didin Didin; Survianti Survianti; Haedar Akib (Universitas Negeri Makassar, 2022)
The village has the authority to regulate its own area according to the abilities and potential of the community in order to achieve prosperity and equitable distribution of economic capabilities. This research is a qualitative descriptive study that aims to determine the Effectiveness of Village Fund Allocation Management in Salo Dua Village, Maiwa District, District. To achieve this goal, the informants in this study were the Village Head, Village Secretary, Village Treasurer, and 2 (two) Communities. Collecting data using observation, interview, and documentation techniques. The results of the study indicate that the Effectiveness of Village Fund Allocation Management in Salo Dua Village, Maiwa District, Enrekang Regency has been effective. It can be seen from the results of the study that the Village Fund Allocation in its use is prioritized for office operational costs, village government income and allowances, etc. If you have excess then the funds can be used for development costs. From the results of the study, it can also be seen from the planning process that the planning carried out was carried out with the preparation of a work plan. In the implementation process, the recording and use of the Village Fund Allocation has been carried out properly and on target. Likewise with the administrative process, the Village Treasurer has also done his job well by using the Siskeudes application. The reporting process has been carried out on time. Likewise, the accountability process has followed all stages in accordance with the applicable laws and regulations.